Magneto‐Ionics in Annealed W/CoFeB/HfO2 Thin Films. Issue 36 (11th July 2022) - Pachat, Rohit; Ourdani, Djoudi; Syskaki, Maria‐Andromachi; Lamperti, Alessio; Roy, Subhajit; Chen, Song; Pietro, Adriano Di; Largeau, Ludovic; Juge, Roméo; Massouras, Maryam; Balan, Cristina; van der Jagt, Johannes Wilhelmus; et al.
Abstract: The magneto‐ionic modulation of the Dzyaloshinskii–Moriya interaction (DMI) and the perpendicular magnetic anisotropy (PMA), in W/CoFeB/HfO2 stacks annealed at different temperatures and for varying annealing times, are presented in this work. A large modulation of PMA and DMI is observed in the systems annealed at 390 and 350 °C, whereas no response to voltage is observed in the as‐grown samples. A strong DMI is only observed in the samples annealed at 390 °C for 1 h, while PMA is present for all annealing times at temperatures of 390 and 350 °C. Magnetic properties including domain wall velocity improve drastically with increasing the annealing temperature and time, while the magneto‐ionic reversibility is increasingly compromised. The changes in PMA and DMI induced by the gate voltages in the samples annealed at 390 °C are permanent, while partial reversibility is only observed for the samples annealed at 350 °C for short times. This dependence of reversibility on post‐grown annealing has been associated to the influence of crystallization on ion mobility. These results show that a compromise between the enhancement of the magnetic properties and the magneto‐ionic performance could be needed in systems requiring annealing to develop PMA and DMI. Abstract : The magneto‐ionic modulation of the Dzyaloshinskii–Moriya interaction and perpendicular magnetic anisotropy, in W/CoFeB/HfO2 stacks annealed at different temperatures and for varying annealing times, are presented. A strong dependence of the magneto‐ionic reversibility on post‐grown annealing is observed and it is associated to the influence of crystallization on ion mobility.